Perceived satisfaction with HIV care and its association with adherence to antiretroviral therapy and viral suppression in the African Cohort Study - Nancy Somi (BMC, 2021)
Abstract Background Increased availability of HIV care over the past decade has dramatically reduced morbidity and mortality among people living with HIV (PLWH) in sub-Saharan Africa. However, perceived and experienced barriers to care, including dissatisfaction with services, may impact adherence and viral suppression. We examined the associations between satisfaction with HIV care and antiretroviral therapy (ART) adherence and viral load suppression. Methods The African Cohort Study (AFRICOS) is a prospective observational study conducted at PEPFAR-supported clinics in four African countries. At enrollment and twice-yearly study visits, participants received a clinical assessment and a socio-behavioral questionnaire was administered. Participants were classified as dissatisfied with care if they reported dissatisfaction with any of the following: waiting time, health care worker skills, health care worker attitudes, quality of clinic building, or overall quality of care received. Robust Poisson regression was used to estimate prevalence ratios and 95% confidence intervals (CIs) for associations between satisfaction with care and ART adherence and between satisfaction with care and viral suppression (viral load < 1000 copies/mL). Results As of 1 March 2020, 2928 PLWH were enrolled and 2311 had a year of follow-up visits. At the first annual follow-up visit, 2309 participants responded to questions regarding satisfaction with quality of care, and 2069 (89.6%) reported satisfaction with care. Dissatisfaction with waiting time was reported by 177 (7.6%), building quality by 59 (2.6%), overall quality of care by 18 (0.8%), health care worker attitudes by 16 (0.7%), and health care worker skills by 15 (0.7%). After adjusting for age and site, there was no significant difference in viral suppression between those who were satisfied with care and those who were dissatisfied (aPR: 1.03, 95% CI 0.97–1.09). Satisfaction with HIV care was moderately associated with ART adherence among AFRICOS participants (aPR: 1.09; 95% CI 1.00–1.16). Conclusions While patient satisfaction in AFRICOS was high and the association between perceived quality of care and adherence to ART was marginal, we did identify potential target areas for HIV care improvement, including reducing clinic waiting times.